Key Opinion Leader Reality: The Key To Successful B2b Digital Marketing? - Ni Made Pradnya Manik Wulandewi; Agus Fredy Maradona (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
KOLs are increasingly using social media to implement digital marketing strategies. This research was conducted in the social context of business-to-business (B2B) sector companies in Indonesia. The study focused on the massive digital marketing activities independently carried out by employees as internal parties of the company, on their personal marketing content on LinkedIn. Consequently, employees are regarded as KOL marketing actors who can cultivate aspects of trust and expertise. This, in turn, affects the credibility of the employees themselves as well as the credibility of the company in the eyes of customers. The results of this study will serve as a practical guide for B2B company leaders. It will help them evaluate key opinion leader strategies through marketing content presented by employees. This will maximize credibility and the success of digital marketing. It will align with the changing market and increasingly dynamic customer needs. The findings of this study, as well as the ensuing discussions, have provided a comprehensive understanding of the challenges associated with leveraging employees as KOLs in marketing endeavors. These challenges manifest in the context of content activities on the LinkedIn platform and pertain to integrity, relevance, accessibility, and market response. The challenge of integrity is related to the consistency of digital presence, time management, honesty in conveying information and data in every piece of content, and transparency in explaining interests in becoming a KOL while being an employee and the face of the company.  The challenge of relevance lies in meeting the needs and interests of a professional audience, obtaining company data, and synchronizing marketing trends and case studies with content creation techniques. The challenge of accessibility stems from the company's inadequate support and conflicts of interest, leading to actions without formal direction.